Introduction: Harold Pinter's Transmedial Histories. Issue 3 (2nd July 2020) - Bignell, Jonathan; Davies, William
Abstract : This article introduces the special issue by exploring the transmediality of Harold Pinter's work. By examining Pinter's texts across television, radio and cinema, as well as theatre, this article argues that both Pinter's formal experimentation and development as a cultural figure are intimately connected to his consistent practice of working across a variety of media.